Impact Of Product Quality And Price On Online Marketplace Consumer Purchase Decisions - Nurmalia Nurmalia; Komarun Zaman; Nur Aini Anisa (Penerbit Goodwood, 2026)
Purpose Study: Purpose of this study is to examine how price and product quality influence Indonesian consumers' choices to buy in Qatar. Methodology/approach: Type of study was a quantitative approach with using survey technique. The sample includes 100 Indonesian respondents in Qatar. The data collected with a questionnaire, and data analysis used the PLS-Structural Equation Modeling. Results/findings: The study findings showed that, both individually and in combination, product quality and price significantly and positively influence consumer choices to buy (P<0.05). Product quality is the most dominant factor, with a greater contribution than price. Conclusion: This study concludes that product quality and price significantly and positively influence the purchasing decisions of Indonesian consumers in Qatar on the Ourshopee.com platform. Product quality is the most dominant factor, indicating that reliability, suitability, and durability play a greater role than price in cross-border online shopping decisions. Limitations: First, the most of respondents were women aged 41–50 years who work as housewives, with nationality of Indonesian residency in Qatar. Second, data collection was conducted on only one e-commerce platform, Ourshopee.com, which does not fully represent consumer behavior across other online shopping platforms. Contribution: Within of improving product quality and setting competitive prices will be attract to customers. For further research, it is recommended to explore additional variables such as promotions and consumer trust, as well as testing on other e-commerce platforms to increase the generalizability of the results.